2004
DOI: 10.1136/pgmj.2003.016584
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella: a continuing problem

Abstract: Salmonella was the archetypal food poisoning organism of the 20th century. It achieved a high public profile following the salmonella-in-eggs crisis of 1988–89, but by then had been the subject of public health concern and scientific interest for over a century. Early associated with animal foods, the advent of phage typing in the 1940s began to reveal the complexity of its environmental associations. This paper explores the story of salmonella as a continuing problem in epidemiology, microbiology and public h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In contrast, enteric fever, caused by typhoid Salmonella, is associated with a high morbidity and mortality rate and occurs predominantly in underdeveloped countries (Hardy 2004).…”
Section: Epidemiologymentioning
confidence: 99%
“…In contrast, enteric fever, caused by typhoid Salmonella, is associated with a high morbidity and mortality rate and occurs predominantly in underdeveloped countries (Hardy 2004).…”
Section: Epidemiologymentioning
confidence: 99%
“…In the early 1980s, PT4 overtook PT8 to become the predominant phage type in 1983, comprising 46% of isolations that year. By 1988 PT4 had risen to account for 81% of Salmonella Enteritidis strains isolated [16] and had ended the political career of a prominent government minister [21]. The United Kingdom was not alone; analysis of data submitted to the World Health Organization's Salmonella surveillance system showed that Salmonella Enteritidis in the late 1980s was increasing on several continents, with North America, South America, and Europe appearing to bear the brunt [22].…”
Section: A Brief History Of Nontyphoidal Salmonellosis In the United mentioning
confidence: 99%
“…Salmonella is Gram negative bacterium known worldwide as the causative agent of gastroenteritis, bacteremia and enteric fever . Majority of human gastroenteritis have been attributed to the consumption of Salmonella contaminated eggs and chicken meat .…”
Section: Introductionmentioning
confidence: 99%